PREPARATION OF COPPER COMPLEXES FROM 1-MONOSUBSTITUTED-3-BENZOYLTHIOUREA LIGANDS - Angulo Cornejo, J. (1998)
Ligands type 1-monosustituted-3-benzoylthiourea were prepared using the Hartman-Reuther Method. The copper complexes prepared from these ligands were characterized by ESR, 1 R, and Electronic S pectroscopy, Differential Thermical Analysis, and elemental analysis. These ligands have shown unexpected behavior, forming Copper (11) complexes in which their both N-H groups, were probably deprotonized, with a polymeric structure.